Abū al-Qāsim al-Zajjājī dan Proses Selection-Choice dalam Membangun Argumen Naḥwu: Kajian Uṣūl al-Naḥwi - Lutfi, Mukhammad (Universitas Negeri Jakarta, 2023)
This research focuses on the thought of Abū al-Qāsim al-Zajjājī and his contributions in naḥwu. By using descriptive qualitative approach, it was found that al-Zajjājī, who lived in the third and fourth centuries of the Hijriyah in Baghdad, with the style “khalaṭa al-madhabayn” tradition, compromised the Basrah and Kufah schools, in other terms, selection (ikhtiyār) and choice (intikhāb) opinions his predecessors. Such traditions have a strong contribution in influencing how al-Zajjājī studied and argued. Through selection and choice, al-Zajjājī proves that it is okay to take opinions from any circles, even through selection and choice it can help explain language phenomena as an introduction to classifying them into special discussions and things similar to them with the aim of expressing the language system with not fanatical to any one sect. The history above also plays a role in having a positive impact towards the maturity of naḥwu studies in subsequent generations, namely the Andalusian naḥwu network with all its past opinions then formulates or applies principles to naḥwu which are more mature and established.